2018
DOI: 10.1177/2474126418806148
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Safety and Efficacy of Sutureless Vitrectomy for Combined Epiretinal and Internal Limiting Membrane Removal

Abstract: The purpose of this case series is to evaluate the long-term visual outcomes of patients undergoing epiretinal membrane (ERM) removal combined with internal limiting membrane (ILM) peeling via sutureless vitrectomy. Methods: A retrospective review was conducted of 45 patients (45 eyes) with ERMs treated with 25-gauge pars plana vitrectomy (PPV) from 2010 to 2011. Data assessed included baseline characteristics, preoperative and postoperative best-corrected visual acuity (BCVA), ERM recurrence rate during follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the subset with ERM recurrence, the absence of ILM peeling was one factor associated with recurrence and reoperation. Regarding the long-term implications of this procedure, Ismail and Mason 16 found significant VA improvement after combined ERM and ILM removal over a mean follow-up of 66.3 months. Although the ERM recurred in 26.7% of eyes (12/45), only 1 eye required subsequent ERM removal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the subset with ERM recurrence, the absence of ILM peeling was one factor associated with recurrence and reoperation. Regarding the long-term implications of this procedure, Ismail and Mason 16 found significant VA improvement after combined ERM and ILM removal over a mean follow-up of 66.3 months. Although the ERM recurred in 26.7% of eyes (12/45), only 1 eye required subsequent ERM removal.…”
Section: Discussionmentioning
confidence: 98%
“…10,[13][14][15] In a study of 40 consecutive eyes, Mason et al 1 found significant improvement in VA after ILM peeling (n = 20) vs ERM removal only (n = 20). 16 ILM peeling is also thought to help prevent ERM recurrence by removing the scaf folding for ERM proliferation. 10,13 In a study of 440 eyes receiv ing PPV for ERM removal, Sandali et al 17 found that ILM peeling was the only significant factor in preventing ERM recurrence.…”
Section: Discussionmentioning
confidence: 99%